Idle Talk under the Bean Arbor : A Seventeenth-Century Chinese Story Collection - Ainajushi (Book collections on Project MUSE., 2017)
"Written around 1660, the unique Chinese short story collection Idle Talk under the Bean Arbor (Doupeng xianhua), by the author known only as Aina the Layman, uses the seemingly innocuous setting of neighbors swapping yarns on hot summer days under a shady arbor to create a series of stories that embody deep disillusionment with traditional values. The tales, ostensibly told by different narrators, parody heroic legends and explore issues that contributed to the fall of the Ming dynasty a couple of decades before this collection was written, including self-centeredness and social violence. These stories speak to all troubled times, demanding that readers confront the pretense that may lurk behind moralistic stances. Idle Talk under the Bean Arbor presents all twelve stories in English translation along with notes from the original commentator, as well as a helpful introduction and analysis of individual stories."--Publisher description.